ZERUMBONE, A NATURAL PLANT DIETARY COMPOUND INDUCES EXPRESSION OF INTERLEUKIN-12P70 CYTOKINE IN HUMAN PERIPHERAL BLOOD MONONUCLEAR CELLS - Dash, Swagatika; Ray, Monalisa; Mishra, Abtar; Shahbazi, Sajad; K, Gopinath Achary; Nayak, Sanghamitra; Singh, Shikha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Despite possessing many biological activities as antiproliferative, antioxidant, anti-inflammatory, and anticancerous, and zerumbone lacks any evidence for its immunomodulatory activity. This naturally occurring dietary compound needs to be developed as drug to support therapeutic claims in various infections and diseases. Methods: Hence, in this study, the immunomodulatory effects of zerumbone were investigated by evaluating the effect of this compound toward the lymphocytes proliferation in human peripheral blood mononuclear cells. Results: Lymphocyte proliferation assay showed that zerumbone was able to activate human lymphocytes at dosage-dependent manner at the highest concentration 40 Î¼l/mL. The production of human interleukin-12p70 cytokine in culture supernatant from activated lymphocytes was upregulated by zerumbone at 24 hrs and gradually decreased at 48 hrs. Hence, the study confirms the immunomodulatory activity of zerumbone which play an important role in boosting up the immune system through cytokine production in dosage dependent manner. Conclusion: The study concludes that zerumbone could be used as a lead molecule in herbal therapeutic world as an immunomodulatory drug in the treatment of chronic infections and various autoimmune disorders. Keywords: Zerumbone, Peripheral blood mononuclear cells, Immunomodulation, Cytokine, Lymphocyte proliferation.